Teacher pedagogical skills for organizing and conducting Music lessons - Murotova Dilnavoz Uktamovna (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
The article deals with the pedagogical skills of a music teacher, the organization of all forms of the educational process in the most convenient and effective way, the ability to direct students towards the goals of personal development, the formation of students' worldview, the tendency to socially necessary activities. There is information about the ability to awaken, the results of musical and pedagogical activities in the interests of society, as well as ways to comprehensively develop the personality of young people